2019
DOI: 10.5935/paet.v12.n1.14
|View full text |Cite
|
Sign up to set email alerts
|

Assimilação de carbono em plantas forrageiras

Abstract: ResumoO aumento descontrolado da emissão dos gases de efeito estufa, especialmente o dióxido de carbono (CO 2 ), afetará diretamente as plantas, devido à influência do dióxido de carbono nos processos fotossintéticos. No entanto, as consequências ambientais não se restringem apenas a esse incremento de gases na atmosfera. Deve-se considerar o aumento simultâneo da temperatura do ar e uma redução da qualidade e quantidade dos recursos hídricos. O impacto das mudanças climáticas sobre a agricultura refere-se, pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 20 publications
0
1
0
1
Order By: Relevance
“…Many works have been made using DGCI for measure the correlation between dark green and fertilization, manly with nitrogen and phosphorus. Caturegli et al (2019) found positive correlation when compared the DGCI with doses of nitrogen applied in For Simões et al (2019), is extremely important to quantify incident radiation during plant development, in order to evaluate their effects in various physiological functioning processes, in addition, it is possible to establish management practices that enable better use of this resource by species of grass, which contributes to a specific aesthetic expectation.…”
Section: Resultsmentioning
confidence: 99%
“…Many works have been made using DGCI for measure the correlation between dark green and fertilization, manly with nitrogen and phosphorus. Caturegli et al (2019) found positive correlation when compared the DGCI with doses of nitrogen applied in For Simões et al (2019), is extremely important to quantify incident radiation during plant development, in order to evaluate their effects in various physiological functioning processes, in addition, it is possible to establish management practices that enable better use of this resource by species of grass, which contributes to a specific aesthetic expectation.…”
Section: Resultsmentioning
confidence: 99%
“…Centrosema molle y Kikuyo presentaron el valor más alto con 272.81 y 199.46 μmol mol -1 respectivamente. Esto indicaría que estas dos especies forrajeras tienen una menor fijación de Ci al momento de realizar la fotosíntesis debido al proceso de foto-respiración (Tolbert, 1980;Ogren, 1984), especialmente Centrosema molle que al tener un metabolismo C3 se ve favorecida con el aumento de este gas en el sitio activo del Rubisco (Simões et al, 2009). El Ci alto en Kikuyo, que tiene un metabolismo C4, posiblemente se deba al que ha desarrollado mecanismos de adaptación para ambientes de clima cálido (Taiz y Zeiger, 2010).…”
Section: Intercambio De Gasesunclassified